Spanish screen fiction : between cinema and television - Smith, Paul Julian (Contemporary Hispanic and Lusophone cultures., 2009)
This book argues that cinema and television in Spain only make sense when considered together as twin vehicles for screen fiction. The Spanish audiovisual sector is now one of the most successful in the world, with feature films achieving wider distribution in foreign markets than nations with better-known cinematic traditions and newly innovative TV formats, already dominant at home, now widely exported. Beyond the industrial context, which has seen close convergence of the two media, this book also examines the textual evidence for crossover between cinema and television at the level of narrative and form.